Evaluasi Pemberdayaan Masyarakat Melalui Pengelolaan Peternakan Sapi Perah di Kampung Susu Lawu Kelurahan Sarangan Kacamatan Plaosan Kabupaten Magetan - Nihayatus Sholichah; Charity Oktoliya (Asketik)
Community empowerment through the management of dairy cattle is one of the flagship programs of the Magetan Regency Government which aims to improving the economy of the people of Kampung Susu Lawu who incidentally are dairy farmers so that farmers can spread their wings in marketing the livestock products they have managed through this empowerment after that. This paper means to reveal and analyze data: 1) the process of community empowerment through the management of dairy farms in the Susu Lawu village, Sarangan sub-district, Plaosan sub-district, Magetan district, and 2) community empowerment evaluation through the management of dairy farms in the Susu Lawu village, Sarangan sub-district, Plaosan sub-district. magnet district. This paper was conducted using a qualitative case study approach. Data collection techniques used are: (1) observation, (2) interviews, and (3) documentation. This paper had result that indicate if: (1) The process of Community Empowerment through the management of dairy farms in the Susu Lawu Village, Sarangan Sub-district, Plaosan District, Magetan Regency is generally quite mature in terms of planning by selecting activities based on the priority needs of community groups. In general, its implementation can support the success of the Empowerment Program through the management of dairy farms and improve the community's economy. (2) Evaluation through the management of dairy farms in the Susu Lawu Village, Sarangan Sub-district, Plaosan District, Magetan Regency is quite successful in developing skills and increasing the income of community groups.